2017
DOI: 10.1080/08977194.2017.1392945
|View full text |Cite
|
Sign up to set email alerts
|

Serum from CCl4-induced acute rat injury model induces differentiation of ADSCs towards hepatic cells and reduces liver fibrosis

Abstract: Cellular therapies hold promise to alleviate liver diseases. This study explored the potential of allogenic serum isolated from rat with acute CCl injury to differentiate adipose derived stem cells (ADSCs) towards hepatic lineage. Acute liver injury was induced by CCl which caused significant increase in serum levels of VEGF, SDF1α and EGF. ADSCs were preconditioned with 3% serum isolated from normal and acute liver injury models. ADSCs showed enhanced expression of hepatic markers (AFP, albumin, CK8 and CK19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Immortalized cells were cultured in Opti-MEM medium supplemented with 10% FBS. In order to determine the HPC population, we compared the corresponding mRNA expression profile of genes encoding (1) HPCs and hepatic specific markers, such as α-fetoprotein ( AFP ), hepatocyte nuclear factor 4 α ( HNF4A ), and alanine aminotransferase ( ALAT ) [21]; (2) HPCs and cholangiocyte-specific markers ( SOX9 ) [22] and epithelial cell adhesion molecule ( EPCAM ) [16]; (3) adipose-derived mesenchymal stem cell (ASCs) markers, such as CD105 and CD90 [23]; as well as an endothelial cell specific marker, platelet and endothelial cell adhesion molecule 1 ( PECAM1 ) [24]. We found that similarly to whole liver tissue, cultured HPCs expressed HNF4A and ALAT.…”
Section: Resultsmentioning
confidence: 99%
“…Immortalized cells were cultured in Opti-MEM medium supplemented with 10% FBS. In order to determine the HPC population, we compared the corresponding mRNA expression profile of genes encoding (1) HPCs and hepatic specific markers, such as α-fetoprotein ( AFP ), hepatocyte nuclear factor 4 α ( HNF4A ), and alanine aminotransferase ( ALAT ) [21]; (2) HPCs and cholangiocyte-specific markers ( SOX9 ) [22] and epithelial cell adhesion molecule ( EPCAM ) [16]; (3) adipose-derived mesenchymal stem cell (ASCs) markers, such as CD105 and CD90 [23]; as well as an endothelial cell specific marker, platelet and endothelial cell adhesion molecule 1 ( PECAM1 ) [24]. We found that similarly to whole liver tissue, cultured HPCs expressed HNF4A and ALAT.…”
Section: Resultsmentioning
confidence: 99%
“…After incubation with serum from rats with acute CCl 4 injury, ADMSCs demonstrated polygonal morphology and expressed AFP, ALB, and CK8 and other hepatocyte markers. Moreover, ADMSCs preconditioned with serum from rats with acute CCl 4 injury significantly improved liver function and reduced liver fibrosis in CCl 4 -induced liver fibrosis, as demonstrated by higher expression of hepatic and pro-survival markers and improvement in liver structure [110]. Exposure to basic fibroblast growth factor obviously upregulated the proliferation and differentiation of ADMSCs in vitro and enhanced the ability of ADMSCs to suppress the progression of liver fibrosis via elevation of HGF expression, promotion of HSC apoptosis, and enhancement of hepatocyte proliferation [83].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Waterman et al 64 in rats with CCl 4 -induced liver fibrosis. 66 In addition, pre-treatment with inflammatory factors also contributes to improving MSC-based therapeutic effects. Although IFN-γ and a multiple cytokine cocktail consisting of IFN-γ, TGF-β and retinoic acid had no effect on the immunomodulation of MSCs in vivo, they significantly enhanced the capacity of MSCs to inhibit the proliferation of CD4+ T cells and CD8+ T cells and the production of IFN-γ.…”
Section: Pre-treatments With An Altered Microenvironment For Msc-bamentioning
confidence: 99%